2022
DOI: 10.1200/jco.21.02478
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following GD2-Directed Postconsolidation Therapy for Neuroblastoma After Cessation of Random Assignment on ANBL0032: A Report From the Children's Oncology Group

Abstract: PURPOSE Postconsolidation immunotherapy including dinutuximab, granulocyte-macrophage colony-stimulating factor, and interleukin-2 improved outcomes for patients with high-risk neuroblastoma enrolled on the randomized portion of Children's Oncology Group study ANBL0032. After random assignment ended, all patients were assigned to immunotherapy. Survival and toxicities were assessed. PATIENTS AND METHODS Patients with a pre-autologous stem cell transplant (ASCT) response (excluding bone marrow) of partial respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…ANBL0032 (enrolled 2001-2015) was conducted by COG. [3][4][5] A total of 1,328 patients were randomly or nonrandomly assigned to postconsolidation therapy comprising dinutuximab, RA, sargramostim, and aldesleukin (excluding n 5 112 initially randomly assigned to RA alone). Patients were required to have previously completed high-risk…”
Section: Study Populationsmentioning
confidence: 99%
“…ANBL0032 (enrolled 2001-2015) was conducted by COG. [3][4][5] A total of 1,328 patients were randomly or nonrandomly assigned to postconsolidation therapy comprising dinutuximab, RA, sargramostim, and aldesleukin (excluding n 5 112 initially randomly assigned to RA alone). Patients were required to have previously completed high-risk…”
Section: Study Populationsmentioning
confidence: 99%
“…Data from the non-randomized extension of the registration trial demonstrated lower grade 3-4 hematologic adverse events in sargramostim cycles vs IL-2 cycles. 27 Other studies demonstrated the benefit of adding dinutuximab plus sargramostim to chemotherapy for relapsed/ refractory HR-NB, 82,84,85 including patients previously treated with anti-GD2 therapy. 84,85 A more recent study explored earlier use of dinutuximab with GM-CSF as part of induction therapy in HR-NB and showed promising end-of-induction objective response rates of up to 87%.…”
Section: Clinical Datamentioning
confidence: 99%
“…Dinutuximab concentrations were measured in plasma on Days 4 and 7 of Cycle 1 dinutuximab infusion and prior to start of Cycle 2 infusion. Samples were analysed using a validated electrochemiluminescence method at BioAgilytix Labs, Durham, NC, as previously published [9].…”
Section: End Pointsmentioning
confidence: 99%
“…This analysis was performed using a validated electro chemiluminescent method (Bioagilytix Labs, Durham, NC). A three-step process of screening assay, confirmatory assay, and titration assay was utilised, as previously published [9].…”
Section: End Pointsmentioning
confidence: 99%
See 1 more Smart Citation